Gingival Biopsy to Detect Mosaicism in Overgrowth Syndromes: Report of Two Cases of Megalencephaly-Capillary Malformation Syndrome with Periodontal Anomalies. (14th September 2020) - Marty, Mathieu; Bonnaud, Carole; Jones, Natalie; Longy, Michel; Vaysse, Frédéric; Bieth, Eric; Bailleul-Forestier, Isabelle
Abstract : Background . Megalencephaly-capillary malformation (MCAP) is a rare overgrowth syndrome caused by postzygotic activating mutations in the PIK3CA gene. Aim . To illustrate the benefits of gingival biopsy in the genetic diagnosis of overgrowth syndromes. Design . Gingival biopsy was performed on a 13-year-old patient and a 16-year-old patient with MCAP and who suffered from periodontal disease. PIK3CA sequencing was performed on DNA extracted from gingival biopsies, blood, and saliva. Results . Pathogenic p.Glu365Lys and p.Glu545Asp PIK3CA mutations were found in the gingival biopsies with an allelic frequency of 22% and 35%, respectively, while they were undetectable in blood or saliva. The genetic diagnosis of MCAP through detection of PIK3CA somatic mosaicism in a periodontal biopsy is unprecedented. Conclusions . Considering the tissue distribution and level of somatic mosaicism for PIK3CA mutation, the composite embryologic origin of periodontium and its high fibroblast cell content make it an ideal target for molecular analysis in overgrowth syndromes, and multidisciplinary approach including paediatric dentists should be encouraged. In addition, our clinical findings suggest that periodontal disease is part of the MCAP phenotypic spectrum and should be systematically investigated.